PENGARUH PEMBERIAN DOSIS PUPUK KANDANG AYAM DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL JAGUNG (Zea mays L.) : Kata kunci: Jagung, Pupuk Kandang Ayam, Pupuk NPK Mutiara - RAHMAD MAHENDRA SARWIJIWO; Priyono, Priyono; Siswadi, Siswadi (innofarm, 2023)
The research entitled "The Effect of Dosing of Chicken Manure and NPK Fertilizer on the Growth and Yield of Corn (Zea mays L.)" was to determine the effect of NPK fertilizer and chicken manure on the development and yield of maize (Zea mays L.). This research was conducted at the Tohudan Horticultural Seeds Garden in Colomadu, Karanganyar Regency, from October to February 2022. In this study, the setting for the experimental location was Complete Randomized Block Design (RAKL) with two components repeated three times. With factor 1 there are 4 levels of chicken manure (K), with a K0 of 0 tons/ha. K1 = 5 tonnes/ha 10 tonnes per acre for K2. K3 comes in 20 tonnes per hectare. The dosage of Mutiara NPK fertilizer (M) was divided into 4 levels with a ratio of 2, with M0 equaling 0 kg/ha. M1= 150 Kg/ha M2= 300 Kg/ha M3= 600 Kg/ha. The research data were evaluated by analysis of variance and the BNJ test at the 5% level. Measurements included plant height, number of leaves, weight of wet and dry stover, cob and husk weight, dry shell weight, and weight of 100 seeds. Judging from plant height, number of leaves, weight of wet stover, and weight of 100 seeds, the results showed that K fertilizer with a K2 dose of 10 tons/ha got maximum results, while a K3 dose produced 20 tons/ha. has the maximum yield compared to the weight of dry stover, dry shell, and cobs with and without husks. The dose of NPK M3 fertilizer of 600 kg/ha gave the best results for almost all criteria when combined with plant height and number of leaves. This specification contains the weight of 100 seeds, wet stover, dry stover, cobs without skin, and dry stover. Keywords: Corn, Chicken Manure, Pearl NPK Fertilizer